Association Between Nitric Oxide, Oxidative Stress, Eryptosis, Red Blood Cell Microparticles, and Vascular Function in Sickle Cell Anemia - Nader, Elie; Romana, Marc; Guillot, Nicolas; Fort, Romain; Stauffer, Emeric; Lemonne, Nathalie; Garnier, Yohann; Skinner, Sarah Chambers; Etienne-Julan, Maryse; Robert, Mélanie; Gauthier, Alexandra; Cannas, Giovanna; et al. (Frontiers in Immunology, 2020)
Chronic hemolysis, enhanced oxidative stress and decreased nitric oxide (NO) bioavailability promote vasculopathy in sickle cell anemia (SCA). Oxidative stress and NO are known to modulate eryptosis in healthy red blood cells (RBCs), however their role in SCA eryptosis and their impact on the genesis of RBC-derived microparticles (RBC-MPs) remains poorly described. RBC-MPs could play a role in vascular dysfunction in SCA. The aims of this study were to evaluate the roles of oxidative stress and NO in eryptosis and RBC-MPs release, and to determine whether RBC-MPs are involved in vascular dysfunction in SCA. Markers of eryptosis and oxidative stress, plasma RBC-MPs concentration and arterial stiffness were compared between SCA and healthy (AA) individuals. In-vitro experiments were performed to test: 1) the effects of oxidative stress (antioxidant: n-acetylcysteine (NAC); pro-oxidant: cumene hydroperoxide) and NO (NO donor: sodium nitroprusside (SNP); NO-synthase inhibitor (L-NIO)) on eryptosis, RBC deformability and RBC-MP genesis; 2) the effects of SCA/AA-RBC-MPs on human aortic endothelial cell (HAEC) inflammatory phenotype and TLR4 pathway. Eryptosis, RBC-MPs, oxidative stress and arterial stiffness were increased in SCA. NAC increased RBC deformability and decreased eryptosis and RBC-MPs release, while cumene did the opposite. SNP increased RBC deformability and limited eryptosis, but had no effect on RBC-MPs. L-NIO did not affect these parameters. Arterial stiffness was correlated with RBC-MPs concentration in SCA. RBC-MPs isolated directly from SCA blood increased adhesion molecules expression and the production of cytokines by HAEC compared to those isolated from AA blood. TLR4 inhibition alleviated these effects. Our data show that oxidative stress could promote eryptosis and the release of RBC-MPs that are potentially involved in macrovascular dysfunction in SCA.